Stability and Behaviour of Rotationally Symmetric Harmonic Maps From A Ball Into A Sphere - Chriestie Montolalu (d\'Cartesian: Jurnal Matematika dan Aplikasi, 2016)
Rotationally Symmetric Harmonic Maps from a Ball into a Sphere has been studied before. The systems conducted in this study can be analyzed further by checking its stability and its behavior in the system. This paper will show how to determine the stability of the system and its behaviour by reducing it into a damped pendulum equation differential equation. Keywords: Â Rotational symmetry, Harmonic maps, Stability, Damped pendulum equation.